2020
DOI: 10.21203/rs.3.rs-65542/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Construction of a risk prediction model for subsequent bloodstream infection in intestinal carriers of carbapenem-resistant Enterobacteriaceae: a retrospective study in hematology department and intensive care unit

Abstract: Background To establish a risk prediction model for carbapenem-resistant Enterobacteriaceae (CRE) bloodstream infection (BSI) in intestinal carriers. Methods CRE screenings were performed every two weeks in hematology department and intensive care unit (ICU). Patients with positive CRE rectal swab screening were identified using electronic healthcare records from 15 May 2018 to 31 December 2019. All CRE strains were collected and identified. Carriers who developed CRE BSI were compared with those who did not… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…A previous study showed that CRE isolates in Miami‐Dade County were predominantly K. pneumoniae 20 . Consistent with previous studies, the main carbapenem‐resistant bacteria in bloodstream infections among rectal carriers was K. pneumoniae (73.8% of the cases) 21 . A recent study on 702 patients suggested that carriers of carbapenemase‐producing K. pneumoniae may have an increased likelihood of prolonged carriage 22 …”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…A previous study showed that CRE isolates in Miami‐Dade County were predominantly K. pneumoniae 20 . Consistent with previous studies, the main carbapenem‐resistant bacteria in bloodstream infections among rectal carriers was K. pneumoniae (73.8% of the cases) 21 . A recent study on 702 patients suggested that carriers of carbapenemase‐producing K. pneumoniae may have an increased likelihood of prolonged carriage 22 …”
Section: Discussionsupporting
confidence: 62%
“…20 Consistent with previous studies, the main carbapenem-resistant bacteria in bloodstream infections among rectal carriers was K. pneumoniae (73.8% of the cases). 21 A recent study on 702 patients suggested that carriers of carbapenemaseproducing K. pneumoniae may have an increased likelihood of prolonged carriage. 22 A previous Chinese study found that 37.1% of intestinal CRKP carriers developed clinical CRKP infections; additionally, ICU admission was an independent risk factor for subsequent clinical infections among intestinal CRKP carriers.…”
Section: Discussionmentioning
confidence: 99%
“…Although there were few studies on this mechanism, one study reported that tigecycline exposure increased the risk of carbapenem resistance Enterobacteriales BSI might be due to intestinal flora disorder. 54 The specific mechanisms need more research. To our knowledge, tigecycline has a large volume of distribution and high concentration in gallbladder, colon and pulmonary tissue.…”
mentioning
confidence: 99%